Análisis del nivel de cumplimiento del perfil profesional y su relación con el desarrollo de competencias expuestas en el diseño curricular en el Octavo Semestre de la Carrera de Biología, Química y Laboratorio, de la Facultad de Ciencias de la Educación Humanas y Tecnologías, periodo octubre 2015- febrero 2016 - Pintag Chuto, Carlos Alberto (2016)
The research problem goes as follow: Do the skills developed by the eighth semester students affect the professional profile proposed in the current curriculum? Nodaway, mankind requires highly trained professionals to perform teaching for social, scientific and technological development, so the University of Chimborazo should develop an appropriate professional profile to accomplish all these requirements. A Professional refers to a set of roles, knowledge, abilities and skills, attitudes and values in a professional according to the geo-socio-economic-cultural development of the context where conditions interact. So the aim of the research was to analyze the skills developed by the eighth semester students in relation to the proposed professional profile in the current curriculum. A non-experimental study that was conducted without the deliberate manipulation of variables. In surveys applied to students of Biology, Chemistry and Laboratory, 67% do not know about the professional profile and do not feel qualified to practice their profession successfully, therefore the importance to develop the necessary skills to improve professional profile